2018
DOI: 10.1007/s13187-018-1340-x
|View full text |Cite
|
Sign up to set email alerts
|

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting

Abstract: Engaging community members in efforts to reduce cancer-related health disparities through community mini-grant programs has been shown to have meaningful impact. A predominantly African-American church in South Carolina was awarded a community mini-grant to increase awareness about colorectal cancer (CRC) screening among disproportionally high-risk African-American communities through culturally appropriate arts-based cancer education. The church's pastor, health and wellness ministry, and drama ministry creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This study has limitations similar to those reported in other evaluations of mini-grant programs (Abildso et al, 2019;Friedman et al, 2019;Perry et al, 2020). First, because the mini-grants were focused at the organizational or community level, we did not measure change at the individual level.…”
Section: > > Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This study has limitations similar to those reported in other evaluations of mini-grant programs (Abildso et al, 2019;Friedman et al, 2019;Perry et al, 2020). First, because the mini-grants were focused at the organizational or community level, we did not measure change at the individual level.…”
Section: > > Discussionmentioning
confidence: 83%
“…Mini-grants, also known as microfunds, have gained traction as an innovative way to build community capacity for health promotion as, even with small amounts of funding, they provide a mechanism for community-driven approaches (Bobbitt-Cooke, 2005; Hartwig et al, 2006). Mini-grants have been used to fund rural churches and worksites to disseminate evidence-based nutrition programs (Honeycutt et al, 2012), African American churches to offer arts-based education to increase awareness of the importance of colorectal cancer screening (Friedman et al, 2019), community-based cancer survivor organizations to increase physical activity among cancer survivors (Perry et al, 2020), economic development organizations (Abildso et al, 2019), community coalitions (Kelly et al, 2019) to improve access to healthy food and physical activity, and schools to increase youth physical activity (Moore et al, 2016). Although existing studies point to the potential of mini-grants to improve community health, few have an explicit focus on promoting and evaluating PSE changes.…”
mentioning
confidence: 99%
“…The South Carolina CPCRN (SC-CPCRN) Collaborating Center has been continually funded since 2002 (with the exception of the 2004–2009 funding cycle) and is now in its fourth cycle [ 3 ]. The SC-CPCRN’s Community Health Intervention Program (CHIP) awards $10,000 grants to community/faith-based organizations that have a clinical partner and that propose to implement evidenced-based strategies and interventions for cancer prevention and control [ 4 – 7 ]. Connecting community members to institutional resources through mini-grants is a recognized strategy to translate the content expertise of academics with the contextual expertise of community members to collaboratively study and act to address health disparities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Central to mini-grant awards are strong existing collaborators, communication, and engagement among trusted collaborators, including the community-based organizations [ 9 ]. Engaged participants and their influence on their community-based organization (i.e., social, religious, occupational) have demonstrated communities’ diversity and conditions for successful partnerships with researchers and funders [ 4 , 10 , 12 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation